2020
DOI: 10.1177/1060028019896638
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety, and Costs of Dolutegravir/Abacavir/Lamivudine Single-Tablet Regimen in a Real-Life Cohort of HIV-1 Adult Infected Patients

Abstract: Background: Real-life data on single-tablet regimen (STR) dolutegravir/abacavir/lamivudine (DTG/ABC/3TC) is scarce, and concerns about DTG neuropsychiatric adverse events (NP-AEs) have recently arisen. Objective: To explore the effectiveness and safety, in particular NP-AEs, of DTG/ABC/3TC in a cohort of HIV-1 adult infected patients. Pill burden, adherence to this STR, and the impact of switching on costs were also evaluated. Methods: This was an observational, retrospective study. The study population includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…We reported adverse effects attributed to DTG in 19.7%, whereas in other studies adverse effects in 35%, 39% and 42.2% of patients have been reported. 8,11,15 Discontinuation rates due to neuropsychiatric effects were reported in 5.6% of patients by Hoffman et al, and in 6.9% by Cid-Silva et al, whereas only 1 patient reported depression after starting DTG which did not lead to discontinuation in this study. 16,17 SACP centre demonstrated prompt initiation of ARV and maintained a steady supply of ARVs.…”
Section: Discussioncontrasting
confidence: 47%
“…We reported adverse effects attributed to DTG in 19.7%, whereas in other studies adverse effects in 35%, 39% and 42.2% of patients have been reported. 8,11,15 Discontinuation rates due to neuropsychiatric effects were reported in 5.6% of patients by Hoffman et al, and in 6.9% by Cid-Silva et al, whereas only 1 patient reported depression after starting DTG which did not lead to discontinuation in this study. 16,17 SACP centre demonstrated prompt initiation of ARV and maintained a steady supply of ARVs.…”
Section: Discussioncontrasting
confidence: 47%
“… 43 , 46 , 47 The increase in serum creatinine during DTG treatment is due to inhibition of the renal organic cation transporter (OCT) 2 which reduces the tubular secretion of creatinine. 46 Only a small proportion of DTG dose (< 1%) is excreted unchanged in the urine; therefore, currently, no dosage adjustments are recommended for DTG in patients with renal impairment. 48 In our study, the mean creatinine level of patients was in a normal range.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, InSTI-based regimens are currently recommended by major international guidelines as first-line therapy [8,9] and they are increasingly used for treatment optimization in order to improve short-and long-term tolerability, reduce drug-drug interactions and improve convenience (e.g. reduced pill burden and/or dosing frequency) of ART [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%